(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
One of the basic reasons why reading is important is that it helps you grow mentally, emotionally, and psychologically. Every book provides you an opportunity to learn and explore new ideas. Reading books increases your knowledge and makes you smarter.